2018
DOI: 10.1021/acschembio.8b00875
|View full text |Cite
|
Sign up to set email alerts
|

CellFy: A Cell-Based Fragment Screen against C-Type Lectins

Abstract: Fragment-based drug discovery is a powerful complement to conventional high-throughput screening, especially for difficult targets. Screening low-molecular-weight fragments usually requires highly sensitive biophysical methods, because of the generally low affinity of the identified ligands. Here, we developed a cell-based fragment screening assay (cellFy) that allows sensitive identification of fragment hits in a physiologically more relevant environment, in contrast to isolated target screenings in solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 41 publications
(76 reference statements)
1
23
0
1
Order By: Relevance
“…Weak affinity chromatography was developed as a tool to screen hits in FBDD ( Duong-Thi et al, 2011 ). Fragment-based screening was also carried out using cell-based assays ( Szõllõsi et al, 2015 ; Schulze et al, 2018 ). A study showed that fragments reacting with cysteine residues were able to identify proteins that formed interactions with these compounds ( Backus et al, 2016 ).…”
Section: Fragment Screening Methodsmentioning
confidence: 99%
“…Weak affinity chromatography was developed as a tool to screen hits in FBDD ( Duong-Thi et al, 2011 ). Fragment-based screening was also carried out using cell-based assays ( Szõllõsi et al, 2015 ; Schulze et al, 2018 ). A study showed that fragments reacting with cysteine residues were able to identify proteins that formed interactions with these compounds ( Backus et al, 2016 ).…”
Section: Fragment Screening Methodsmentioning
confidence: 99%
“…Although multivalence is in general the most employed strategy to overcome the poor intrinsic affinities of C-type lectins, computational and screening studies have gradually directed the attention to other novel DC-SIGN ligands. [147,148] Indeed, previous works have already found nonsugar fragments with remarkably low affinities compared to monosaccharides (μM; Figure 6A and B), [149] and some of them are able to efficiently trigger cell signaling when conjugated to a protein scaffold. [150] Fragment screening analyses have identified other potentially druggable sites in the CRD architecture, [151] which could be exploited for the design of more potent DC-SIGN modulators ( Figure 6C).…”
Section: Relevant Interacting Monosaccharides and Glycansmentioning
confidence: 99%
“…Recently, a promising screening method has been developed and simultaneously tested with DC-SIGN and langerin. [148] The method enables a better evaluation of the binding potencies under physiological conditions, directly on the CLR-containing cells ( Figure 10A). Detection of hits is achieved by direct competition between a reference fluorescent ligand (FITC-dextran) and the tested fragments.…”
Section: Langerinmentioning
confidence: 99%
“…2 The development of functional carbohydrate mimics has been tackled either by structure-based design, 1,[3][4][5][6][7][8][9][10][11][12][13] or by discovery campaigns, often planned taking advantage of microarray technology. [14][15][16] The latter approach has been frustrated by the cumbersome synthesis of oligosaccharides, that severely limits the diversity and the number of compounds that can be rapidly generated.…”
Section: Introductionmentioning
confidence: 99%